κ/ι-Carrageenan Blends in Plant Capsules: Achieving Harmony Between Mechanical and Disintegration Properties - Zhenyu Liu; Chuqi He; Zhibin Yang; Qing Zhao; Yuting Dong; Jing Ye; Bingde Zheng; Ranjith Kumar Kankala; Xueqin Zhang; Meitian Xiao (Marine Drugs)
The fast-disintegrating capsules rapidly disintegrate in various physiological environments, ensuring therapeutic efficacy. The formulation of plant-based capsules with balanced mechanical and fast disintegration characteristics continues to present technical challenges in pharmaceutical development. In this study, natural marine polysaccharides were utilized to achieve both rapid disintegration and excellent mechanical properties by combining κ-Carrageenan (κ-C) and ι-Carrageenan (ι-C). Additionally, the selection of KCl + NaCl mixed coagulants, along with the evaluation of their types, mass fractions, and ratios, enhanced the mechanical properties and transmittance of the capsules. FTIR analysis revealed that the membrane with a 5:5 κ-C/ι-C ratio formed hydrogen bonds, which were beneficial to its fast disintegration. SEM analysis revealed a dense microstructure in this formulation, contributing to its improved mechanical properties. Finally, this study hypothesizes that the disintegration behaviors of the capsules exhibited significant pH dependence, with ion exudation predominating in pH 1.2 and pH 7.0 media, while swelling dominated under pH 4.5 and pH 6.8 media. The prepared carrageenan blend-based capsules exhibited fast disintegration properties while maintaining excellent mechanical and barrier properties, thereby broadening the application of plant-based capsules in the field of medicine.